Scenario building for service design at Montemor-o-Velho - Franqueira, Teresa (2013)
This paper aims to showcase an ongoing service design project for the Montemor-o-Velho municipality, which is integrated in Ruas de Cultura (Streets of Culture), a project with a wider scope. The proposal of Montemor-o-Velho City Hall promotes the regeneration of several central urban spaces, through the dinamization of 3 axes: 1 – One unit where the Artistic Residencies will be installed; 2 – A Technological Centre and companies’ incubator; 3 – Several spaces dedicated to social activities. The ID+ participates with 2 types of intervention. The first one is centred around the development of actions/tools that can promote the implementation of an organizational and space management model based on the following premises: active incentives to sharing experiences, sharing knowledge and tasks; and a second one focused on the creation of an identity system for the project. This article aims to highlight the axis of service design actions/tools’ development, with a particular emphasis on participatory design. Based on visual representation tools characteristic of the design activity, several scenarios will be outlined in order to promote a strategic debate between all stakeholders, some of which will be detailed in this paper. The tools which will allow for the collaboration and participation of future users of these spaces will also be developed in the project.